El tratamiento - Hayder, Mo; Cáceres, Carmen M.; Barba, Andrés, 1975-; Hayder, Mo. (Madrid : Siruela, 2014)
Detective Jack Caffery returns to investigate a brutal attack on a London couple and the mysterious disappearance of their young son, a crime that brings him face to face with nightmarish memories of his own past.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Caffery, Jack -- (Fictitious character) -- Fiction; Police -- Fiction; Abduction -- Fiction; Murder -- Fiction; Detective and mystery fiction; Electronic books